Deliberative Democracy and the New Social Movement: A Case from the Bojonegoro Media - Muhamad Sulhan (Komunikator, 2019)
The post-reform social movement is an interesting topic study. The nature of the movement which was not merely ideological vis a vis with the repressive style of the new order, this movement continued to look for unique formulations related to the negation of subject-objects. In that context the role of the media becomes an interesting element to examine. The existence and position of the media becomes a necessity in a social movement. Non-governmental organizations (NGOs) have used the media in such a way as to achieve its’ goals. Apart from a fluctuating level of success, the process of integrating the movement of substances with the medium that mediates the achievement of goals becomes an interesting object of study. This article intends to elaborate on how far the meaning and dynamics of  new media, focusing on two websites of social movements in Bojonegoro in achieving NGO objectives. Using narrative text analysis, this paper attempts to parse in simple terms the two pages of the website according to the information system settings and models created by the government of Bojonegoro Regency, East Java. In his analysis, this study uses Habermas's view of the deliberatif discourse of the dam model as a theoretical framework.